A high-tech start-up's debt financing strategy: Implications for valuing soft information - Hyunsung D. Kang (The Journal of Entrepreneurial Finance (JEF), 2017)
How does entrepreneurial financing differ from traditional financing? This study sheds new light on this central question of entrepreneurial finance literature by exploring the distinctive role of soft information in a high-tech start-up's debt financing. Entrepreneurial investors can obtain soft information from strong relationships with potential investees and use the information to evaluate and select promising investees. Using a dataset on 683 SBA 7(a) loan activities involved with information technology based start-ups, this study provides empirical evidence that high-tech start-ups tend to experience a lower rate of default if they are located close to the lending banks and the lending banks are of considerable size. These conditions allow the lending banks to collect and utilize soft information regarding high-tech start-ups in an efficient manner.
Keywords: D82; G14; L26; 650; high-tech start-up; entrepreneurial finance; debt financing; soft information; SBA